2018
DOI: 10.3805/eands.10.22
|View full text |Cite
|
Sign up to set email alerts
|

Effects of antiepileptic drugs on microglial properties

Abstract: Purpose:To elucidate the effects of antiepileptic dr ugs (AEDs) on micr oglial cytokine pr oduction, polarization, and morphology. Methods: MG6, an immor talized mouse micr oglial cell line, was stimulated with lipopolysaccharides (LPS) and the levels of pro-inflammatory cytokines were measured by enzyme linked immunosorbent assay, quantitative polymerase chain reaction (q-PCR), and intracellular staining using flow cytometry. M1 and M2 signatures of microglia after polarization were assessed using quantitativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…However, we cannot exclude that LEV affects genes, morphological parameters or functions of microglia/macrophages that we did not measure. LEV has been shown to affect some properties of immortalized microglial cell lines ( Shima et al., 2018 ; Itoh et al., 2019 ), although it should be noted that such cell lines differ from primary microglia in many respects, including in their responses to LPS stimulation ( Butovsky et al., 2014 ; Das et al., 2016 ). For the following reasons we also consider it most likely that the effects of tau reduction on inflammation-related gene expression resulted indirectly from the modulation of neuronal activities.…”
Section: Discussionmentioning
confidence: 99%
“…However, we cannot exclude that LEV affects genes, morphological parameters or functions of microglia/macrophages that we did not measure. LEV has been shown to affect some properties of immortalized microglial cell lines ( Shima et al., 2018 ; Itoh et al., 2019 ), although it should be noted that such cell lines differ from primary microglia in many respects, including in their responses to LPS stimulation ( Butovsky et al., 2014 ; Das et al., 2016 ). For the following reasons we also consider it most likely that the effects of tau reduction on inflammation-related gene expression resulted indirectly from the modulation of neuronal activities.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro studies on microglial cells as mediators of inflammation have demonstrated that topiramate, a second generation AED, decreased the release of IL-1β, IL-6 and TNF-α [ 144 ] . Other AEDs such as levetiracetam, gabapentin, and phenobarbital showed slight modification in cytokine production [ 145 ] . The first generation AED valproic acid, was shown to increase IL-6 and TNF-α production in LPS-induced microglial cells [ 145 ] , which contrasts with in vivo results where TNF-α and IL-1β were decreased after valproic acid treatment [ 143 ] .…”
Section: Discussionmentioning
confidence: 99%
“…Other AEDs such as levetiracetam, gabapentin, and phenobarbital showed slight modification in cytokine production [ 145 ] . The first generation AED valproic acid, was shown to increase IL-6 and TNF-α production in LPS-induced microglial cells [ 145 ] , which contrasts with in vivo results where TNF-α and IL-1β were decreased after valproic acid treatment [ 143 ] . It was also demonstrated that the AED levetiracetam suppressed neuroinflammation and phagocytosis in a pilocarpine induced SE model [ 143 ] .…”
Section: Discussionmentioning
confidence: 99%